Enhancement of emotional intelligence-related competencies of successors in family businesses - Dźwigoł-Barosz, M. (Економічний вісник Донбасу, 2017)
The following article presents issues related to the enhancement of emotional intelligence-related competencies of family business successors. A particular emphasis was put on emotional intelligence which constitutes an essential element of the successors’ competencies. The author of the article provided examples of actions and methods to enhance the emotional intelligence-related competencies, on the grounds of studies by other researches as well as her own research. Readers’ attention was drawn to the impact of parents (senior members of the family) on actions and enhancement of emotional competencies of successors. У даній статті представлено питання, пов'язані з посиленням емоційних розумових здібностей сімейних бізнес-наступників. Особливий акцент був зроблений на емоційному інтелекті, який являє собою істотний елемент компетенції наступників. Автор статті навів приклади дій та методів для підвищення компетентності, пов'язаної з емоційним інтелектом, на основі аналізу попередніх досліджень, а також її власних досліджень. Увагу в статті було звернуто на вплив батьків (старших членів сім'ї) на дії і підвищення емоційної компетентності наступників. В данной статье представлены вопросы, связанные с усилением эмоциональных умственных способностей семейных бизнес-преемников. Особый акцент был сделан на эмоциональном интеллекте, который представляет собой существенный элемент компетенции преемников. Автор статьи привел примеры действий и методов для повышения компетентности, связанной с эмоциональным интеллектом, на основе анализа предыдущих исследований, а также ее собственных исследований. Внимание в статье было обращено на влияние родителей (старших членов семьи) на действия и повышение эмоциональной компетентности преемников.